2015
DOI: 10.1080/19393210.2014.981601
|View full text |Cite
|
Sign up to set email alerts
|

Furanic compounds and furfural in different coffee products by headspace liquid-phase micro-extraction followed by gas chromatography–mass spectrometry: survey and effect of brewing procedures

Abstract: In this study, the levels of furan, 2-methylfuran, 2,5-dimethylfuran, vinyl furan, 2-methoxymethyl-furan and furfural in different coffee products were evaluated. Simultaneous determination of these six furanic compounds was performed by a head space liquid-phase micro-extraction (HS-LPME) method. A total of 67 coffee powder samples were analysed. The effects of boiling and espresso-making procedures on the levels of furanic compounds were investigated. The results showed that different types of coffee samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…The studies published to date have shown no significant differences in furan and alkylfuran levels in caffeinated versus noncaffeinated beverages (Becalski et al., ). Instant coffees manufactured by spray drying seem to contain relatively lower amounts of furan versus more mildly freeze dried instant coffees (Chaichi et al., ). Furthermore, the manufacturing process, particularly the degree of aroma retention, will most likely be a decisive factor in final furan/methylfuran content, as the volatile coffee aroma fraction will contain a significant proportion of the furan present.…”
Section: Update On Occurrence Of Furan and Alkylfuransmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies published to date have shown no significant differences in furan and alkylfuran levels in caffeinated versus noncaffeinated beverages (Becalski et al., ). Instant coffees manufactured by spray drying seem to contain relatively lower amounts of furan versus more mildly freeze dried instant coffees (Chaichi et al., ). Furthermore, the manufacturing process, particularly the degree of aroma retention, will most likely be a decisive factor in final furan/methylfuran content, as the volatile coffee aroma fraction will contain a significant proportion of the furan present.…”
Section: Update On Occurrence Of Furan and Alkylfuransmentioning
confidence: 99%
“…Other determinants of furan in the cup are the brewing method as well as final preparation of the beverage prior to consumption. Furan and 2‐MeF dissipate rapidly upon brewing, with more than 60% 2‐MeF “lost” when brewed with an espresso machine or by boiling (Chaichi et al., ). The same authors reported losses of around 45% when preparing commercial instant coffee (reconstituted at 80 °C with prepared product maintained at 43 °C).…”
Section: Update On Occurrence Of Furan and Alkylfuransmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the aldehydes, furfural was identified at a high level in the distillates D1 and D2. This compound is formed during processes that involve heating or roasting, e.g., roasting of coffee beans and/or distillation, due to degradation of fermentable pentose sugars, caused by heating in acid conditions, and/or Maillard reaction [34][35][36]. Thus, high amounts of furfural might be attributed to the presence of high quantities of residual pentose sugars due to unfavourable fermentation conditions of the substrate.…”
Section: Volatile Composition Of Fermented and Spirit Beveragesmentioning
confidence: 99%
“…Various studies regarding the effect of Turkish coffee traditions and coffee houses on social life as well as studies on traditional equipment used for preparing and serving Turkish coffee and also studies regarding the health effects of Turkish coffee, its antioxidant capacity and determination of furanic compounds and furfural in Turkish coffee have been conducted [1][2][3][4][5][6][7][8][9][10][11]. For this purpose, the headspace volatiles of Turkish-style Boiled Coffee, brewed from light, medium and dark roasted, ground Arabica coffee beans, isolated by solid phase micro extraction (SPME) were analysed by gas chromatography-mass spectrometry (GC/MS) analysis and descriptive sensory analysis was performed..…”
Section: Introductionmentioning
confidence: 99%